Development and validation of a novel cellular senescence-related prognostic signature for predicting the survival and immune landscape in hepatocellular carcinoma - Sun, Rui; Wang, Xu; Chen, Jiajie; Teng, Da; Chan, Shixin; Tu, Xucan; Wang, Zhenglin; Zuo, Xiaomin; Wei, Xiang; Lin, Li; Zhang, Qing; Zhang, Xiaomin; et al. (Frontiers in Genetics, 2022)
Background: Cellular senescence is a typical irreversible form of life stagnation, and recent researches suggested that lncRNA could regulate the occurrence and development of various tumors through this way. In the present study, we attempted to construct a novel signature for predicting the survival of patients with hepatocellular carcinoma (HCC) and the associated immune landscape, based on senescence-related long noncoding ribonucleic acids (srlncRNAs). Method: Expression proﬁles of srlncRNAs in 424 patients with HCC were retrieved from the TCGA database (https://portal.gdc.cancer.gov). Differentially expressed (DE) srlncRNAs were identiﬁed were recognized using Lasso regression and Cox regression analyses. Receiver operating characteristic curve (ROC), Kaplan-Meier (KM) analysis, and Cox regression analyses, nomogram, and calibration curves were performed to verify the prediction efficiency of the signature. The risk groups of Gene set enrichment analyses (GSEA), immune analysis, and prediction of the half-maximal inhibitory concentration (IC50) were also analyzed. Quantitative real-time polymerase chain reaction (qPCR) was performed to validate the expression levels of AC026412.3, AL451069.3, and AL031985.3 in normal hepatic and HCC cell lines. Results: We identified 3 srlncRNAs, and patients were divided into high-risk and low-risk groups based on the risk score. Low-risk patients had a significantly longer survival time than high-risk patients (p < 0.001). The area under the curve of the signature to predict 1-, 3-, 5-year survival was 0.754, 0.675, and 0.670, respectively. The risk score correlated with tumor grade, AJCC stage, and T stage. The risk score was still signiﬁcant after univariate and multivariate Cox regression analyses. Based on the results, a nomogram model was constructed to accurately predict patient prognosis. The risk score also correlated with immune cell inﬁltration status, immune checkpoints expression, and sensitivity to chemotherapeutic drugs. The results of qPCR revealed that AC026412.3 and AL031985.3 were signiﬁcantly upregulated in hepatoma cell lines. Conclusion: The novel senescence-related lncRNAs (AC026412.3, AL451069.3, and AL031985.3) signature may provide insight into the new therapies and prognosis prediction for HCC patients.